Memodelkan Impor Beras Menggunakan Regresi Data Panel - Eka N Kencana; Darma Arnawa; Ketut Jayanegara (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Abstract Rice is one of the world’s most important commodities. The Food and Agri-cultural Organizations estimates about 90 percent of the world’s rice is produced bycountries in the Asian continent with the rice production centers located in the ASEANregion. As an agricultural country, Indonesia is ranked third in the world rice producersafter China and India, and in the first rank of ASEAN rice producers. However, Indone-sia along with other producing countries in ASEAN also import rice. This article aimsto model rice imports from 5 ASEAN countries. Using data from FAO for the period2009–2018, 3 types of Panel Data Regression models were applied to model rice imports.The results of the analysis show Random Effect Model (REM) is the most appropriatemodel for rice imports in 5 ASEAN countries with the difference for two consecutiveyears import, consumption, and rice production was used as explanatory variables .Keywords: import, panel data, random effect, regression, rice.